India contemporary design : fashion, graphics, interiors - Patel, Divia (2011)
Between 2000-2008 India's economic and political ascendancy were charted in the worlds press. This period of dynamism ushered in an increased sense of confidence, aspiration and pride in being Indian. This book is about the response of the design community to India's changing environment. It focuses on fashion, graphic and interior design as metaphors of the complex networks that constitute globalisation within key metropolitan centres of India. Examined within the context of their production and consumption, and through their economic, social, political and cultural underpinnings, a picture emerges which conveys how designers grapple with issues of identity and globalisation, nationhood and modernity, ethics and commerce.
Includes bibliographical references (pages 250-255).
Keywords: Design -- India -- History -- 21st century; Fashion -- India -- History -- 21st century; Interior decoration -- India -- History -- 21st century; Graphic arts -- India -- History -- 21st century